Investigating the choice of teaching methods employed by English literature teachers in Malaysian secondary schools: student-centered or teacher-centered? / Jun Jaslin Johari - Johari, Jun Jaslin (2013)
In 1999, the Ministry of Education made it a requirement that English literature be taught to all secondary school students. One of the five English periods is allocated to the teaching of literature. It was since then that the English literature component was madepart of the Integrated Curriculum for Secondary School (KBSM). The incorporation of this component has however raised many issues regarding the teaching and learning of the subject. Among the popularly-discussed issues is the choice of methods in teaching the subject , whether it is teacher-centered or student-centered. As such, this study aimed at looking at the perceptions and preferences of secondary school English teachers in selecting and employing the most accommodating approach. Additionally, significant difference in perceptions was also observed by choosing teaching experience as a variable. The findings indicated that teachers showed a greater tendency to use the student-centered approaches compared to the teacher-centered approaches when teaching English literature. Apart from that, a number of factors that contribute to such preferences were also identified. Among the factors identified include communication skills enhancement, exciting and meaningful learning experience, catering for better students as well as less expectation on teachers. The implications of the secondary school English teachers ' preferences were also identified.